2018
DOI: 10.1007/s00382-018-4512-9
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the influence of local and remote anthropogenic aerosols on South Asian monsoon daily rainfall characteristics

Abstract: Wet and dry periods within the South Asian summer monsoon season can have acute societal impacts. Recent studies have identified changes in daily rainfall characteristics of the monsoon, but the underlying causes are poorly understood. In particular, although the dominant role of anthropogenic aerosols in shaping historical changes in seasonal-mean monsoon rainfall has been documented, their influence on daily-scale rainfall remains unconstrained. Using an ensemble of single-forcing climate simulations, we fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 98 publications
(157 reference statements)
1
32
0
Order By: Relevance
“…While aerosols and GHG have been the most widely‐studied external forcings on the South Asian summer monsoon, the role of widespread agricultural expansion and intensification in driving the 20th century weakening are starting to get attention (Krishnan et al, ; Lee et al, ; Niyogi, Kishtawal, Tripathi, & Govindaraju, ; Paul et al, ; Shukla et al ; D. Singh, McDermid, et al, ). Recent studies have shown the potential for land‐cover change from agricultural expansion to contribute to the weakening of the monsoon.…”
Section: Observations Changes In Precipitation Processes and Their Atmentioning
confidence: 99%
See 1 more Smart Citation
“…While aerosols and GHG have been the most widely‐studied external forcings on the South Asian summer monsoon, the role of widespread agricultural expansion and intensification in driving the 20th century weakening are starting to get attention (Krishnan et al, ; Lee et al, ; Niyogi, Kishtawal, Tripathi, & Govindaraju, ; Paul et al, ; Shukla et al ; D. Singh, McDermid, et al, ). Recent studies have shown the potential for land‐cover change from agricultural expansion to contribute to the weakening of the monsoon.…”
Section: Observations Changes In Precipitation Processes and Their Atmentioning
confidence: 99%
“…Unlike most other regions where GHG are likely to be the dominant forcing in the future, South Asia will continue to experience these multiple, diverse, and spatially heterogeneous forcings (Figure ), which have likely already influenced several characteristics of the monsoon (Bollasina, Ming, & Ramaswamy, , ; Douglas, Beltrán‐Przekurat, Niyogi, Pielke, & Vörösmarty, ; Guo, Turner, & Highwood, ; Lau & Kim, ; Z. Li et al, ; Meehl, Arblaster, & Collins, ; Paul, Ghosh, Oglesby, Pathak, & Chandrasekharan, ; Puma & Cook, ; Ramanathan et al, ; Ramanathan & Carmichael, ; Salzmann, Weser, & Cherian, ; Shukla, Puma, & Cook, ; D. Singh, Bollasina, Ting, & Diffenbaugh, ). Regional aerosols are projected to increase for at least the next few decades and agricultural activities will continue to intensify, to meet the rising food and energy demands of the growing population (Defries, Bounoua, & Collatz, ; R. Kumar et al, ; Tilman et al, ; van Vuuren et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On a global scale, atmospheric DMS concentrations are predicted to increase by 41 % with a tripling of atmospheric CO 2 , increasing mean aerosol optical depth (AOD) by 3.5 % and cooling the Northern and Southern Hemisphere by 0.4 and 0.8 K, respectively (Gabric et al, 2013). Other studies simulate a global reduction of the DMS flux by 10 %-18 % (Kloster et al, 2007;Six et al, 2013) and 48 % (Schwinger et al, 2017) under various ocean acidification scenarios by the end of the 21st and 22nd centuries, respectively. Modelled scenarios predict an additional global warming of 0.23-0.48 K due to a decline in DMS-derived sulfate aerosols and cloud albedo (Schwinger et al, 2017;Six et al, 2013), although significant regional variability in the response of DMS emissions to climate perturbations was present.…”
Section: Dms Sea-to-air Fluxmentioning
confidence: 99%
“…Other studies simulate a global reduction of the DMS flux by 10 %-18 % (Kloster et al, 2007;Six et al, 2013) and 48 % (Schwinger et al, 2017) under various ocean acidification scenarios by the end of the 21st and 22nd centuries, respectively. Modelled scenarios predict an additional global warming of 0.23-0.48 K due to a decline in DMS-derived sulfate aerosols and cloud albedo (Schwinger et al, 2017;Six et al, 2013), although significant regional variability in the response of DMS emissions to climate perturbations was present. In the Southern Ocean, DMS emissions increased in response to warming, counteracting the predicted regional decrease in emissions in response to OA (Schwinger et al, 2017).…”
Section: Dms Sea-to-air Fluxmentioning
confidence: 99%
See 1 more Smart Citation